Pengaruh Nilai Taksiran, Ujrah Dan Promosi Terhadap Minat Nasabah Dalam Menggunakan Produk Pembiayaan Gadai Emas Syariah : (Studi Kasus Pada Bank Riau Kepri Syariah Cabang Pembantu Batam) - Septhani Eka Putri (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2022)
The Islamic gold pawn is one of the products in banking that is loved by the public in overcoming short-term capital shortages, coupled with the increasing gold price which has increased significantly during the pandemic, stepping on the price of 1 million / gram. This becomes interesting when the world economy experiences a decline and losses, the price of gold actually increases significantly. Therefore, gold has a pretty promising business potential, not least in terms of gold pawning. The purpose of this study is to determine the effect of the estimated value, ujrah and promotion on customer interest in using Islamic gold pawn financing products. This study uses a quantitative approach and uses primary data. The population used in this research are Bank Riau Kepri Syariah CAPEM Batam customers who use Islamic gold pawn financing products. The sample used in this study was purposive sampling method. Analysis of the data used in this study was SmartPLS 2.0. The results of this study indicate that there is a significant positive effect of the estimated value on customer interest with an O value of 0.185146 and a T-Statistic value of 14,465,931. There is a significant positive effect of ujrah on customer interest with an O value of 0.708490 and a T- Statistic value of 93.002.845. There is a significant positive effect of promotion on customer interest with an O value of 0.118095 and a T-Statistic value of 10,599.935. Keywords: Estimated Value, Ujrah, Promotion, Interests